Proceso de entrada y salida del mercado: análisis del mercado de la franquicia - Bordonaba Juste, Mª Victoria; Lucía Palacios, Laura; Polo Redondo, Yolanda (Cuadernos de Estudios Empresariales, 2006)
The order of market entry is considered as a source of gaining and maintaining competitive advantages (Michael, 2003; Robinson and Min, 2002; Alpert and Kamis, 1995). Pioneering strategy provides the greater advantages (Boulding and Christen, 2003). However, these articles present some limitations because the research is addressed to incumbent firms, not including nonsurvival firms in the analysis. Moreover, previous research uses the market share as a performance measure and other critics are addressed to the market selected or the product categories studied, which, in most of the cases, are consumer durable goods in maturity markets (VanderWerf and Mahon, 1997; Shankar et al., 1998; Lieberman and Montgomery, 1998). On the other hand, the opposite results are found in the literature suggesting a second mover strategy or deferring the entry as a suitable decision through which firms can gain competitive advantages (Bates, 2001; Cottrell and Sick, 2002; Mirjam van Praag, 2003). Thus, this article 1) analyzes the process of market entries and exits in the franchise distribution system by a longitudinal dataset (1995-2002) dealing with survivor bias, and contributes with a study of the nonsurvivors’ characteristics and 2) examines the pioneering advantages against the other entrants (earlyfollowers, late-followers and late-movers) using different measures of performance (economic profitability, sales, gross profit, operating income, added value and cash flow).